Finite element modelling for the dynamic behaviour analysis of a structure with Hi-Lok fasteners / Muhammad Syafiq Aiman Mohd Kahar ... [et al.] - Mohd Kahar, Muhammad Syafiq Aiman; Wan Iskandar Mirza, Wan Imaan Izhan; Abdul Rani, Muhamad Norhisham; Yunus, Mohd Azmi (UiTM Press, 2024)
The number of Hi-Lok fasteners used in the assembly of aircraft structures is very high. For this reason, an efficient modelling technique is required to accurately analyse the dynamic behaviour of the structures. In this study, a modelling technique with special emphasis on Hi-Lok modelling is proposed to analyse the dynamic behaviour of a test structure with Hi-Lok fasteners. Four different finite element (FE) models to represent the test structure with the Hi-Lok fasteners were developed using MSC Software packages. The natural frequencies and mode shapes obtained from the FE models are compared with those of the Experimental Modal Analysis (EMA) in terms of total error, computational time and memory disk usage. It was found that the model D with the simplified beams representing Hi-Lok predicts the dynamic behaviour of the test structure with an accuracy of 96.6% and with comparatively low computational time and memory disk usage. This proposed modelling scheme may provide useful approaches to aircraft researchers and engineers for the dynamic analysis of the structures.